2020
DOI: 10.1101/2020.08.04.235697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver x receptor alpha drives chemoresistance in response to side-chain hydroxycholesterols in triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) is challenging to treat successfully because targeted therapies do not exist. Instead, systemic therapy is typically restricted to cytotoxic chemotherapy, which fails more often in patients with elevated circulating cholesterol. Liver x receptors are ligand-dependent transcription factors that are homeostatic regulators of cholesterol, and are linked to regulation of broad-affinity xenobiotic transporter activity in non-tumor tissues. We show that LXR ligands confer chemoth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To confirm if the protein bands were LXRa variants, we first performed siLXRa treatments in cell lines. Using previously validated [7] siRNA duplexes (Origene trisilencers) against LXRα and LXRβ we found that the protein bands predicted by size to be α1, α2, α3, a5, and b1 were all significantly reduced by targeted siRNA in all cell lines tested (all p<0.05; SF7). Note: a4 and b4 were not expressed in cell lines so could not be validated in this way.…”
Section: Bands Representing Lxr Variants Were Reduced By Targeted Sirnamentioning
confidence: 88%
See 4 more Smart Citations
“…To confirm if the protein bands were LXRa variants, we first performed siLXRa treatments in cell lines. Using previously validated [7] siRNA duplexes (Origene trisilencers) against LXRα and LXRβ we found that the protein bands predicted by size to be α1, α2, α3, a5, and b1 were all significantly reduced by targeted siRNA in all cell lines tested (all p<0.05; SF7). Note: a4 and b4 were not expressed in cell lines so could not be validated in this way.…”
Section: Bands Representing Lxr Variants Were Reduced By Targeted Sirnamentioning
confidence: 88%
“…We previously reported that LXRα expression is positively correlated to target gene expression in ER-negative patients who had relapsed and/or died due to their disease (Event patients) but not those who survive disease free (No Event patients) [7]. Here, we tested the hypothesis that differential LXR splice variant expression between cancers may contribute to disease aetiology via their ability to control expression of gene targets.…”
Section: Lxr Splice Variants Are Differentially Correlated With Expression Of Target Genes In Event and No Event Patientsmentioning
confidence: 98%
See 3 more Smart Citations